Dynamic space, complex contexts - Martínez Sánchez, Maria José (Urban, 2016)
IntroductionThe present article deals with the proposal of a new perspective on understanding urban spaces: based upon movement analysis. Not only a theoretical frame is presented, but also the basis so as to develop this new urban narrative through a movement analysis and notation. KeywordsCorpocidade; corpografía; cartography; kinetography; movement